The Effect of Dividend Policy and Environmental Social Governance on Company Performance with Moderation of Good Corporate Governance in IDX LQ45 Companies - Wicaksono, Henry; Muchtar, Susy (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This study aims to analyze the effect of dividend policy and environmental social governance (ESG) on company performance as measured by Tobins’q and stock prices with moderation of Good Corporate Governance (GCG) in companies listed on the LQ45 Index of the Indonesia Stock Exchange (IDX) for the period 2019-2023. The research sample using purposive sampling method obtained 20 companies that entered the criteria to be sampled. The results showed that dividend policy has no effect on company performance as measured by tobin’s q and stock price, ESG has no effect on company performance as measured by tobin’s q and stock price, financial leverage has no effect on company performance as measured by tobin’s q, but financial leverage has an influence with a negative relationship direction on company performance as measured by stock price, company size has a negative and significant effect on company performance as measured by tobin’s q, but company size has a positive influence on company performance as measured by tobin’s q, GCG moderation proves to have no effect between dividend policy on company performance as measured by Tobin’s q, but GCG moderation proves to have a negative effect between dividend policy on company performance as measured by stock prices, GCG moderation has a negative effect between ESG on company performance as measured by Tobins’ q, but GCG moderation proves to have no effect between ESG on company performance as measured by stock prices. This research has important implications for companies and investors. For companies, it is important to implement an optimal dividend policy and commit to ESG principles to improve company performance. For investors, these findings can help in making investment decisions by considering factors such as dividend policy, ESG, and corporate governance.